The sustainability impacts and opportunities of reverse osmosis (RO) plants on the quadruple bottom line perspective: a case of the Eastern Cape Province, South Africa - Mfihlo, Cwayita (Rhodes University, Faculty of Commerce, Rhodes Business School)
Water scarcity is a pressing global issue exacerbated by factors such as population growth, urbanisation, and climate change. This challenge is particularly acute in water-stressed regions where a substantial portion of the world's population resides. Desalination, particularly through reverse osmosis (RO), has emerged as a viable solution to address this demand, providing a stable and high-quality water supply without overburdening natural freshwater ecosystems. This research focuses on the sustainability impacts and opportunities of RO desalination plants, specifically examining the Cerebos SA plant in Gqeberha and the Amatola Water plant at Bushman's River, to provide insights into their environmental, social, economic, and governance impacts and opportunities from a life cycle perspective. In addition to investigate the key sustainability considerations relevant to RO desalination plants to potentially augment available water provision sources in the Eastern Cape. Ten participants were purposively sampled from Ndlambe Municipality, Cerebos S.A, and Amatola Water. Semi-structured interviews and document analysis were used to collect data. The research design was grounded in the post-positivism paradigm, emphasising the incorporation of diverse perspectives and the search for valid and reliable evidence within existing phenomena. Three strategies were used to ensure credibility data for this study, these were triangulation, diverse participant selection, and audio interview transcription using Otter.ai. The results from the research offered valuable insights into the sustainability impacts and opportunities of the RO desalination plants from the Life Cycle perspective, although the respondents demonstrated a clear understanding of sustainability, the concept of QBL was less familiar to many. Furthermore, the respondents unpacked QBL impacts and opportunities from a life cycle perspective and augmentation consideration for RO desalination plants. Key recommendations included conducting thorough environmental impact assessments, transitioning to renewable energy sources, energy recovery systems, inventory management, and enhancing community engagement and workforce training. Despite limitations in scope and participant diversity, the findings fill a gap in the literature, offering valuable insights for stakeholders to enhance water provision sustainability.
Keywords: Saline water conversion; Reverse osmosis process; Life cycle assessment; Sustainability; Sustainable development; Social sustainability; Water governance